Situation des femmes dans les industries artistiques et culturelles au Canada : Examen de la recherche (Hill Strategies Research Inc, 2018)
Cet examen recense plus de 250 rapports, articles et documents de sources ontariennes ou canadiennes contenant des données sur les femmes dans six secteurs d’activités artistiques et culturelles : les arts visuels, la danse, le théâtre, la littérature, la musique et les arts médiatiques/sur écran. Une de ses principales constatations est qu’il n’existe pas d’études ayant […]

#moiaussi de l’humour : un an après ? - Paré, Christelle (Le Journal de Québec, 2018)
Le #moiaussi en humour a sonné l'alarme, chiffres à l'appui.

Men's Intrusion, Women's Embodiment: A critical analysis of street harassment - Vera-Gray, F. (Routledge, 2018)
Research on violence against women tends to focus on topics such as sexual assault and intimate partner violence, arguably to the detriment of investigating men’s violence and intrusion in women’s everyday lives. The reality and possibility of the routine intrusions women experience from men in public space – from unwanted comments, to flashing, following and frottage – are frequently unaddressed in research, as well as in theoretical and policy-based responses to violence against women. Often at their height during women’s adolescence, such practices are commonly dismissed as trivial, relatively harmless expressions of free speech too subjective to be legislated against. Based on original empirical research, this book is the first of its kind to conduct a feminist phenomenological analysis of the experience for women of men’s stranger intrusions in public spaces. It suggests that intrusion from unknown men is a fundamental factor in how women understand and enact their embodied selfhood. This book is essential reading for academics and students involved in the study of violence against women, feminist philosophy, applied sociology, feminist criminology and gender studies.

Un an depuis #moiaussi: la contestation dans les oeuvres - CÔTÉ, ÉMILIE (La Presse, 2018)
Le mouvement #moiaussi a inspiré auteurs, artistes et créateurs de toutes les disciplines artistiques. Tour d'horizon.

Musical genius and/or nasty piece of work? Dealing with violence and sexual assault in accounts of popular music’s past - Strong, Catherine; Rush, Emma (Continuum, 2018)
For many years, the mistreatment of women in particular has essentially been normalized in many parts of the music industry. In recent years, however, there has been an increase in women coming forward and telling their stories, and asking that men be held accountable for wrongdoing. This interdisciplinary (sociology and philosophy) paper pursues two key feminist questions prompted by recent developments. Firstly: How has the construction of the history of popular music legitimated the continuation of this situation? ‘Looking back’ historically and sociologically, examples are provided of the legitimation or ignoring of violence against women (VAW) in the history of popular music to date. Secondly: How should we [archivists, historians, heritage curators and popular music educators], from now on, construct the history of popular music in a way that doesn’t legitimate VAW? Turning to ‘look forward’, applied ethics frameworks are used to explore different aspects of this second question.
Keywords: Bibliographie; Nettoyer

Hard facts, soft measures: Gender, quality and inequality debates in Danish film and television in the 2010s - Redvall, Eva Novrup; Sørensen, Inge Ejbye (Journal of Scandinavian Cinema, 2018)
Abstract This article investigates discussions about gender, quality and equality in Danish film and television in the 2010s. Contrary to Sweden, where gender diversity has been part of public debate and formal screen policy since the 2000s, there was little discussion of gender in the Danish screen industry until the Danish Film Institute (DFI) began focusing on diversity as a priority area before the Film Strategy for 2015–18. The article analyses how both DFI and industry players have continuously argued against gender quotas, instead opting for soft measures such as ‘gender declarations’ and initiatives to raise awareness. One of these initiatives was a manifesto, ManusFestet, that used humour to raise questions about gender representation on-screen. The article discusses how a balance between hard facts and soft measures seems to be experienced as a constructive way forward, as long as this combination does in fact facilitate the intended change.
Publisher: Intellect
Keywords: Irina

“The Whole Feminist Taking-Your-Clothes-off Thing”: Negotiating the Critique of Gender Inequality in UK Music Industries - Bennett, Toby (IASPM Journal, 2018)
This article considers the critique of inequality, exploitation and exclusion in contemporary UK music industries, in light of the latter’s growing internal concerns over work-based gender relations. The creative sector’s persistent inequalities are at odds with its professed liberal, egalitarian, meritocratic values and attitudes. Yet, within music’s industrial production cultures, a dismissive postfeminist sensibility has come under pressure through a reflexive critical moment of popular feminist discourse, expressed in trade press critique, between 2013 and the present moment. Drawing from a study of intermediary work in UK major record labels, the article takes a pragmatist approach to documenting and theorizing this critique – alongside institutional mechanisms, like company policies and corporate PR, that respond to it – in terms of growing industrial reflexivity. Tensions over the representation of work, the nature of inequality, intergenerational and epistemic injustice emerge as key themes, with implications for critical research on popular music industries.
Number: 1
Keywords: Industrial Reflexivity; Inequalities; KEYWORDS: Creative labour; Major record labels; Post-feminism.

Écrire le viol (La Presse+, 2018)
Le sujet est délicat. Tellement que plusieurs personnes contactées ont refusé de se prononcer sur cette nouvelle prise de conscience qui découle des mouvements #moiaussi et #agressionnondénoncée. Les romanciers doivent-ils s’autocensurer pour respecter une nou
Section: ARTS

Comment écrire le viol ? - Clément, Éric (La Presse+, 2018)
Le sujet est délicat. Tellement que plusieurs personnes contactées ont refusé de se prononcer sur cette nouvelle prise de conscience qui découle des mouvements #moiaussi et #agressionnondénoncée. Les romanciers doivent-ils s’autocensurer pour respecter une nou
Keywords: Bibliographie; Nettoyer

Représentation du viol en littérature: pour dire quoi? (Le Devoir, 2018)
La représentation gratuite du viol n’est pas sans effet chez les lectrices.

Comment parler des violences faites aux femmes en littérature? - Caillou, Annabelle (Le Devoir, 2018)
Trois spécialistes se penchent sur le sujet. Analyse.
Keywords: Bibliographie; Nettoyer

Une nouvelle décrivant un viol entraîne la démission de la directrice de la revue «XYZ» - Caillou, Annabelle (Le Devoir, 2018)
Vanessa Courville a claqué la porte de la revue consacrée à la nouvelle littéraire.
Keywords: Bibliographie; Nettoyer

Orchestres symphoniques: une parité favorisée par un processus à l'aveugle - Larochelle, Samuel (La Presse, 2018)
Femmes et hommes côte à côte dans les orchestres symphonique d'ici. La question de parité est souvent lié au processus de sélection à l'aveugle des musiciens, une façon de faire qui permet de mettre de l'avant le talent, et ce, peu importe le sexe des artistes.
Keywords: Bibliographie; Nettoyer

Facing Sexual Harassment and Abuse in the Feminizing Museum - trivedi, nikhil; Wittman, Aletheia (Journal of Museum Education, 2018)
Despite the growing number of women in museums, the undervaluing of educational work traditionally associated with women, and labor largely done by women today, persists. This begs the question: in what other ways are women and femmes working in museums undermined despite their growing presence as workers and the emerging centrality of the educational role of museums? In society more broadly, we see how undervaluing women and their labor leads to a spectrum of treatment that can be considered violent. In this spectrum, we include pay and benefit disparities, disempowerment, and marginalization through sexist, homophobic, and transphobic comments and objectification, harassment, threats, verbal, physical, emotional, and financial abuse, and at the far end of the spectrum sexual assault and murder. In this article, we discuss data collected through a survey conducted about incidences of sexual abuse and harassment experienced by museum workers. We explore the results of the survey in relation to the gender-based division of labor and skills among the museum workforce. We look to the responses to this survey as a gauge of how much power women and gender non-conforming people have in their daily work lives in museums and propose actions that could increase empowerment and support.
Keywords: Bibliographie; Myriam; Nettoyer; Sexual violence; feminization; gender equity; labor; museum education; museum workers

'Shocking' level of sexual harassment at music festivals (BBC News, 2018)
Up to 43% of women under 40, who have been to a music festival, say they have faced unwanted sexual behaviour.

Le #metoo de Coeur de pirate - Cassivi, Marc (La Presse, 2018)
Béatrice Martin, alias Coeur de pirate, fera paraître vendredi son quatrième album, En cas de tempête, ce jardin sera fermé, un hommage à Paris qui coïncide avec ses 10 ans de carrière. Une très belle collection de textes sombres et poétiques, sur des musiques lumineuses et entraînantes, où l'auteure-compositrice-interprète évoque des épisodes douloureux de son passé.

Post Weinstein: gendered power and harassment in the media industries - Cobb, Shelley; Horeck, Tanya (Feminist Media Studies, 2018)
Keywords: #MeToo; Bibliographie; Irina; Nettoyer

What sexual harassment in Zentropa tells us about cultural policy post-Weinstein - Sorensen, Inge (Feminist Media Studies, 2018)
Publisher: Routledge _eprint: https://doi.org/10.1080/14680777.2018.1456165
Keywords: Irina

Les humoristes font leur part pour #MoiAussi - Gendron-Martin, Raphaël (Le Journal de Montréal, 2018)
«On aurait pu avoir 40 humoristes dans le spectacle», lance le coanimateur de la soirée, Patrick Groulx.

The music business’s gender pay gap is embarrassing and uncomfortable. It’s time for change. (Music Business Worldwide, 2018)
MBW Contributing Editor, Rhian Jones, gives her take on the news…

900 000 $ pour contrer les agressions sexuelles et le harcèlement dans le milieu culturel québécois - Ministère de la Culture et des Communications (Gouvernement du Québec, 2018)
Keywords: Bibliographie; Nettoyer

A Dance with Many Secrets: The Experience of Emotional Harm from the Perspective of Past Professional Female Ballet Dancers in Canada - Moola, Fiona; Krahn, Alixandra (Journal of Aggression, Maltreatment & Trauma, 2018)
Originating in the Italian and French courts, ballet is an age-old art that fuses aesthetics and athleticism (Wulff, 2008). Despite changing times, ballet masters and mistresses tenaciously hold on to a sense of deep traditionalism. However, some scholars suggest that unwavering devotion to the art may conceal troubled embodied relations and oppressive practices (Gvion, 2008). In this study, we drew on the phenomenological research tradition in an effort to further examine the power relations that play out on the body in the world of Canadian professional ballet (Papaefstathiou, Rhind, & Brakenridge, 2013). Twenty past professional female ballet dancers from across Canada participated in this study. Our dedicated dancers were relentless. They sacrificed body and mind in the pursuit of excellence in a broader cultural context that expected nothing less. The dancers normalized harmful emotional experiences, inappropriate sexual transgressions, and chronic injury (Gvion, 2008). They also described experiences of neglect—and feeling replaceable—after the onset of injury. We have attempted to theorize our findings within the context of embodiment literature and the work of gender theorists. Emboldened by our dancers’ voices, we have shed light—and broken secrets—regarding some of the harmful practices that still characterize professional ballet in Canada. We hope that our work might further continue efforts to democratize power imbalances in professional ballet and ultimately enhance holistic dancer development and health.
Publisher: Routledge _eprint: https://doi.org/10.1080/10926771.2017.1410747

“The Destruction of a Legacy”: Agenda Setting and the Bill Cosby Sexual Assault Allegations - Terán, Larissa; Emmers-Sommer, Tara M. (Sexuality & Culture, 2018)
Utilizing agenda setting theory, this study investigates the Bill Cosby sexual assault allegation scandal and how the scandal is framed by the media. In order to examine if and how varied networks reported differently on the Cosby scandal, sixty articles from three, distinct networks (CNN, FOX News, E!) were analyzed and coded under seven different categories. Results demonstrate a significant difference among the analyzed networks and media frames most reported in the sample for this study. Although all networks address Cosby’s rise and fall of an American hero, agendas set and story frames presented varied. Specifically, CNN highlighted victims’/survivors’ powerful voice whereas E! and FOX News highlighted Cosby’s support from the black community, celebrities and co-stars. Additional results, discussion and future directions follow.
Keywords: Agenda setting theory; Bill Cosby; Mediated communication; Scandal; Sexual assault; Sophie-Anne

Danse #WeToo - Ferron, Geneviève C. (Regroupement québécois de la danse, 2018)
// English version Depuis l’émergence du mouvement #metoo en octobre dernier, plusieurs femmes artistes du Québec ont pris la parole pour dénoncer le harcèlement, l’intimidation et les abus dont elles ont été victimes ou témoins dans le cadre de leur […]
Keywords: Bibliographie; Nettoyer

Danse #WeToo - Pantalacci, Sandrine (Regroupement québécois de la danse, 2018)
// English version Depuis l’émergence du mouvement #metoo en octobre dernier, plusieurs femmes artistes du Québec ont pris la parole pour dénoncer le harcèlement, l’intimidation et les abus dont elles ont été victimes ou témoins dans le cadre de leur […]

Winnipeg comedy club bans discrimination, hatefulness, harassment | CBC News - Gibson, Shane (CBC, 2018)
Wee Johnny’s comedy room posted a sign this week warning that anyone violating a new anti-harassment policy — which bans “sexism, racism, homophobia, transphobia, physical intimidation or any other form of abusive behaviour” — may be asked to leave the club.

L'Université de Montréal fait son mea culpa (La Presse+, 2018)
L’Université de Montréal reconnaît avoir toléré, faute de balises adéquates, des comportements « inacceptables » du professeur Jean Larose, parti à la retraite en 2011 à la suite d’une plainte pour attouchements et harcèlement sexuels qui a été rejetée. Un cas
Section: ACTUALITÉS

EDM and Ecstasy: the lived experiences of electronic dance music festival attendees - Little, Noah; Burger, Birgitta; Croucher, Stephen M. (Journal of New Music Research, 2018)
Attendance at large-scale music festivals has captivated a global interest in these spectacular experiences, yet little is known about the lasting benefits and personal changes individuals incur following this event. This study aims to provide a comprehensive exploration of the lived experiences of individuals who attended a multi-day electronic dance music festival. The present study was primarily interested in the perceived beneficial changes within the individual, following their festival experience. We investigated if first-time festival attendees perceived changes differed to those of returning individuals. Semi-structured qualitative interviews were used to collect data from 12 individuals who attended the 2015 Electronic Daisy Carnival in Las Vegas. Six participants were first-time attendees while the remaining six were individuals returning to the festival. The data was analysed using Thematic Analysis. Within the data emerged the following central themes: (1) escape, (2) communitas, and (3) self-reported changes; there were 10 subthemes. These findings add to the existing body of music festival literature, further contextualizing how music festivals are both experienced, and reflected upon by individuals. Further, this study highlights the potential lasting changes individuals’ experience from attending electronic dance music festivals.
Publisher: Routledge _eprint: https://doi.org/10.1080/09298215.2017.1358286
Keywords: Music festival; electronic dance music; music; social acceptance; social cohesion

“Essential—Passion for Music”: Affirming, Critiquing, and Practising Passionate Work in Creative Industries - Bennett, Toby (The Palgrave Handbook of Creativity at Work, 2018)
This chapter considers “passion” as an enthusiastic orientation to work within creative worlds: work motivated by intense attachments to the products of work and their conditions of production. Drawing on Luc Boltanski’s pragmatic sociology of critique and justification, the chapter argues that the passionate lens most usefully trains our sights on normative questions: not what or how—but why such work is undertaken. Embedded in research on cultural and creative industries, the contemporary recorded music sector is presented as a “passionate” industry in transformation. Interviews with workers, who both criticize and defend their industry, act as a springboard to explore three possible interpretive approaches: affirmative, critical, and pragmatic. Theoretical flexibility is needed to keep “passion” open to future inquiry—particularly regarding inequalities in creative work.

Représentation du viol en littérature: pour dire quoi? - Boisclair, Isabelle (Le Devoir, 2018)
Keywords: Bibliographie; Nettoyer

Sexisme en danse : le mur du silence s’effrite au Québec - Carpentier, Mélanie (Jeu : revue de théâtre, 2018)
Un article de la revue Jeu, diffusée par la plateforme Érudit.
Publisher: Cahiers de théâtre Jeu inc.
Keywords: Bibliographie; Nettoyer

Charte égalité Hommes-Femmes - Centre national des arts du cirque (2018)
Keywords: Sophie-Anne

The Right of One's Own Image in the Recent Cases of Sexual Harassment in Film Industry: Applying the European Theory of Concentric Circles to Celebrities (In Particular, Women) - Corredoira, Loreto (Journal of Information Policy, 2018)
Keywords: Irina

Politique visant à prévenir et à combattre les violences à caractère sexuel - École nationale de cirque - Montréal (2018)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer; Sophie-Anne

Université de Montréal: briser l'omerta - Elkouri, Rima (La Presse, 2018)
Keywords: Bibliographie; Nettoyer

Intégrer les personnes trans en milieu de travail - Fondation émergence; Aide aux Trans du Québec (ATQ) (2018)
Keywords: Bibliographie; Nettoyer

Sexual Harassment and Violence at Music Concerts and Festivals - Heen, Miliaikeala Sj.; Lieberman, Joel D. (Center for Crime and Justice Policy, 2018)
Publisher: 6876
Keywords: Bibliographie; Nettoyer

Code de conduite - Industries créatrices du Canada (lirelecode.ca, 2018)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

The Bystander Moment - Jeremy Earp (Media Education Foundation, 2018)
Keywords: Coffre à outils; À ajouter

"I Didn't Want To Be 'That Girl'": The Social Risks of Labeling, Telling, and Reporting Sexual Assault - Khan, Shamus; Hirsch, Jennifer; Wamboldt, Alexander; Mellins, Claude (Sociological Science, 2018)
This article deploys ethnographic data to explain why some students do not label experiences as sexual assault or report those experiences. Using ideas of social risks and productive ambiguities, it argues that not labeling or reporting assault can help students (1) sustain their current identities and allow for several future ones, (2) retain their social relationships and group afﬁliations while maintaining the possibility of developing a wider range of future ones, or (3) avoid derailing their current or future goals within the higher educational setting, or what we call “college projects.” Conceptually, this work advances two areas of sociological research. First, it expands the framework of social risks, or culturally speciﬁc rationales for seemingly illogical behavior, by highlighting the interpersonal and institutional dimensions of such risks. Second, it urges researchers to be more attentive to contexts in which categorical ambiguity or denial is socially productive and to take categorical avoidance seriously as a subject of inquiry. Substantively, this work advances knowledge of why underreporting of campus sexual assault occurs, with implications for institutional policies to support students who have experienced unwanted nonconsensual sex regardless of how those students may label what happened.

Modèle de politique pour la création d'un milieu de travail sain, respectueux et exempt de discrimination, de harcèlement et de violence - Labine, Lise; Lorquet, Me Sébastien (L’Association des théâtres francophones du Canada, 2018)
L’Association des théâtres francophones du Canada a développé ce modèle de politique pour ses compagnies membres avec l’appui de Théâtre Action.
Keywords: Bibliographie; Nettoyer

Facing (and Fixing) the Problem of Sexual Harassment in Theatre - Lehman, Stefanie Maiya; Morris, Celestine (Southern Theatre, 2018)
Keywords: Bibliographie; Nettoyer; Raphaël

Examining the Embodied Learning Experiences about Gender in Gay and Bisexual Male Actors - McCadden, Ted; Wright, Robin Redmon (2018)
Keywords: Bibliographie; Nettoyer; Raphaël

Navigating the Margins between Consent and Dissent: Mechanisms of Creative Control and Rock Music in Late Socialist Romania - Mogoș, Petrică; Berkers, Pauwke (East European Politics and Societies: and Cultures, 2018)

Enquête sur le portrait sociodémographique et l’égalité homme-femme chez les créatrices et créateurs d’humour au Québec – Sommaire 2018-2: Données sur la perception de l’égalité entre les femmes et les hommes - Paré, Christelle; Brouard, François (Groupe de recherche sur l’industrie de l’humour (GRIH), SCSE/CSES, Sprott Centre for Social Enterprises / Centre Sprott pour les entreprises sociales (SCSE/CSES), Université Carleton, 2018)
Keywords: Bibliographie; Humour; Nettoyer; Sophie-Anne; Types de VACS

Bar Training for Active Bystanders: Evaluation of a Community-Based Bystander Intervention Program - Powers, Ráchael A.; Leili, Jennifer (Violence Against Women, 2018)
Bystander intervention programs are proliferating on college campuses and are slowly gaining momentum as sexual violence prevention programs suitable for the larger community. In particular, bystander intervention programs aimed at bar staff have been developed in a number of locations. This study entails the exploratory evaluation of a community-based bystander program for bar staff. Using a pre–posttest design, this study suggests that evidence surrounding the effectiveness of this program is promising as it decreases rape myths, decreases barriers to intervention, and increases bartenders willingness to intervene. Future research and policy implications are discussed.
Keywords: Camille

Un enseignant de l'École nationale de cirque accusé de crimes sexuels - Radio-Canada (Radio-Canada, 2018)
L'entraîneur Marcelo Berti Marques fait face à quatre chefs d'accusation, entre autres pour avoir envoyé une photo de ses organes génitaux à un de ses anciens élèves de l'École nationale de cirque, à Montréal. Sa présumée victime est soulagée, mais craint qu'il ait fait d'autres victimes.
Keywords: Bibliographie; Nettoyer

The Morality of Musical Men: From Victorian Propriety to the Era of #MeToo - Shaver-Gleason, Linda (2018)
Keywords: Bibliographie; Nettoyer

Reconceptualizing Sexual Harassment, Again Collection: #MeToo and the Future of Sexual Harassment Law - Shultz, Vicki (Yale Law Journal Forum, 2018)
Keywords: Irina

Encouraging Safer and More Supportive Working Practices in Theatre - Society of London Theatre; UK Theatre (2018)
Keywords: Bibliographie; Nettoyer; Raphaël

Performing Arts Training in the Age of #MeToo - Spencer, Jennifer (Voice and Speech Review, 2018)
Keywords: Bibliographie; Nettoyer; Raphaël

Line Drawn Summit and Survey Report - Stone, Meg (Impact, 2018)
Keywords: Bibliographie; Nettoyer; Raphaël

Harassment and bullying in the theatre industry: a report - The Stage (The Stage, 2018)
Keywords: Bibliographie; Nettoyer; Raphaël

The Whole Feminist Taking-Your-Clothes-off Thing”: Negotiating the Critique of Gender Inequality in UK Music Industries - Toby, Bennett (Gender Politics in the Music Industry, 2018)
This article considers the critique of inequality, exploitation and exclusion in contemporary UK music industries, in light of the latter’s growing internal concerns over work-based gender relations. The creative sector’s persistent inequalities are at odds with its professed liberal, egalitarian, meritocratic values and attitudes. Yet, within music’s industrial production cultures, a dismissive postfeminist sensibility has come under pressure through a reflexive critical moment of popular feminist discourse, expressed in trade press critique, between 2013 and the present moment. Drawing from a study of intermediary work in UK major record labels, the article takes a pragmatist approach to documenting and theorizing this critique – alongside institutional mechanisms, like company policies and corporate PR, that respond to it – in terms of growing industrial reflexivity. Tensions over the representation of work, the nature of inequality, intergenerational and epistemic injustice emerge as key themes, with implications for critical research on popular music industries.

L’ordinaire de la violence. Un cas d’atteinte sexuelle sur mineure en milieu artistique - Trachman, Mathieu (Travail, genre et sociétés, 2018)
L’ordinaire est un thème souvent mobilisé dans les études sur les violences de genre. À partir d’un cas d’atteinte sexuelle sur mineure, cet article a pour objectif d’en préciser les enjeux. Il montre en premier lieu que la notion d’ordinaire, qui signifie souvent ce qui est commun à toutes les femmes, gagne à voir son périmètre précisé : dans le cas analysé, le travail artistique, sa dimension vocationnelle, la personnalisation des relations entre professeur et étudiante, les coûts d’entrée dans le métier pour les femmes sont des éléments déterminants. Dans les études féministes, l’ordinaire désigne également les faits de violence qui caractérisent la vie quotidienne des femmes. En distinguant faits, situation et qualification, l’article montre que la qualification de violence implique un sentiment d’anormalité et une réflexivité largement absents dans les situations de violence de genre. Ce hiatus explique l’incertitude souvent inhérente à la qualification de violence et le caractère rétrospectivement énigmatique des situations de violence. L’ordinaire de la violence désigne ainsi moins une évidence occultée qu’un registre de l’expérience où les abus et les agressions sont intégrés dans le cours des choses et normalisés par les protagonistes.
Place: Paris Publisher: La Découverte